On Care-fulness: Critical Creative Expressions of Care in a Feminist Theatre Research Project - Holman Jones, Stacy; Harris, Daniel X; Campbell, Alyson; Myers, Misha; Murray, Peta; Grigor, Mish; Stevens, Ripley (Research in Arts and Education, 2021)
In early 2020, as the first of many COVID lockdowns began across Australia, a collective of feminist and queer performance scholars and artists embarked on the research project Staging Australian Women’s Lives: Theatre, Feminism and Socially Engaged Art. Our aim was to document contributions of womxn theatre makers, while conducting a feminist analysis of strategies used to deal with gender inequality and oppression, on stage and off. While pivoting to the digital and the virtual, we recognised a need to support womxn theatre makers whose lives and livelihoods are thrown into further precarity by the pandemic. This paper speaks to our commitment to bringing together critical theory, arts practices and everyday life in ethical forms and encounters that make visible, recognise and express care for one another and for the work.